Answer:
y = -
![(24)/(7)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2qlzyrkjzgl31mqtz6a7ckb8q7r0b56w1n.png)
Explanation:
Given y varies directly with x then the equation relating them is
y = kx ← k is the constant of variation
To find k use the condition y = 6 when x = - 7
6 = - 7k ( divide both sides by - 7 )
-
= k
y = -
x ← equation of variation
When x = 4 , then
y = -
× 4 = -
![(24)/(7)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2qlzyrkjzgl31mqtz6a7ckb8q7r0b56w1n.png)